Rwanda : Third Review Under the Policy Support Instrument. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Rwanda's Third Review Under the Policy Support Instrument (PSI). Rwanda's performance under the PSI has been satisfactory. The authorities are to be commended for meeting all quantitative assessment criteria. The performance on indicative targets and structural benchmarks was uneven, and it will be important to maintain the momentum of reforms, including on revenue mobilization while strengthening project implementation. Growth in 2015 is expected to remain strong, while the outlook is stable. The cautious fiscal stance and monetary policy are consistent with the need to preserve policy buffers.